Het debat over de staat Israël in de Protestantse Kerk in Nederland - Reuver, Reinier de (Kerk en theologie, 2024)
This article answers Gert van Klinken's question whether there is still a supported view within the Protestant Church in the Netherlands on its relationship to (the state of) Israel. That there are various views within this church regarding the people of Israel in general and the state in particular is evident. The publication of Israel, People, Land and State (1970) made this diversity visible. Yet formal statements and documents of the Protestant Church show that beneath this diversity of voices lies a supported and consistent theological vision. A vision that matures through ongoing theological reflection focuses on the Kingdom of God.